Pengaruh Brand Trust Dan Price Terhadap Keputusan Pembelian Sepatu Fans (Studi Kasus Pada SMAN 1 Habinsaran, Sumatera Utara) - Sagala, Bahari; Aisyah, Nur; Lubis, Adelina (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
This research aims to determine "The Influence of Brand Trust and Price on Fans' Shoe Purchase Decisions (Case Study at SMA N 1 Habinsaran, North Sumatra)". This research uses quantitative research methods with the aim of analyzing the influence between two or more variables. The sample in this research were female students at SMA N 1 Habinsaran. In this research, researchers carried out questionnaires. Test the data in this study using SPSS 22. Based on the results of the partial test (t), brand trust and price have a positive and significant effect on purchasing decisions. In the Determination Coefficient Test (R2), the Adjusted R Square value was 35.9%. This proves that the independent variable has a high ability to explain variations in the dependent variable in this research.